DIGITAL COMPETENCE AS ONE OF THE PROFESSIONAL SKILLS OF A COMPUTER SCIENCE TEACHER - Shekerbekova Ш.Т.; Bakytbekova Ж.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article examines the problem of digital competence of computer science teachers as one of their professional skills. First, an analysis of the definitions given by academic researchers to the concept of digital competence is carried out. The understanding of the digital competence of a teacher is analyzed and systematized. Effective methods for the formation and development of digital competence of a computer science teacher will be found, and ways of use in the field of digital technologies will be given. One of the effective technologies for enhancing educational and cognitive activity in the context of digitalization of education is the use of modern technologies for visualizing educational information. The use of modern technologies for visualizing educational information will allow you to develop, shape your personality, and also have the opportunity to use ready-made resources, creating them in accordance with your needs. Therefore, the use of educational information visualization technologies is implemented as part of three components of digital competencies.